The role of nationality on the pacing of Ironman triathletes - Nikolaidis, P. T.; Kach, I.; Rosemann, T.; Knechtle, B. (Asian Journal of Sports Medicine, 2017)
The aim of the present study was to examine the role of nationality on the pacing of Ironman triathlon (3.8 km swimming, 180 km cycling, and 42.195 km running). Data from 302,535 athletes (women, n = 61,087; men, n = 241,448) competing between 2002 and 2015 in 253 different Ironman triathlon races were analyzed. We examined split times (i.e. swimming, cycling, and running) and transition time, expressed as percentage of the overall race time. Participants were classified into performance groups according to their overall race time: 9 - 10 hours, 10 - 11 hours, 11 - 12 hours, 12 - 13 hours, 13 - 14 hours, 14 - 15 hours, 15 - 16 hours, > 16 hours. Compared to men, women spent relatively less time in swimming (P < 0.001, d = -0.07), running (P < 0.001, d = -0.14) and transition time (P < 0.001, d = -0.11), and more time in cycling (P < 0.001, d = 0.21). Germans were the fastest in both women and men (P < 0.001); Australians, Austrians and Brazilians were also among the four fastest nationalities in both sexes; (b) in women, athletes from New Zealand spent relatively the least time and athletes from Brazil the most on swimming, whereas in men, Australians spent relatively the least time and Austrians the most (P < 0.001); (c) Austrians spent relatively the least time in cycling and British the most in women, whereas Austrians spent relatively the least time and Spanish the most in men (P < 0.001); (d) British spent relatively the least time in running and Australians in women, and Spanish spent relatively the least time and Australians the most in men (P < 0.001); and (e) Australians spent relatively the least time in transition and British the most in women, whereas Australians spent relatively the least time and Irish the most in men (P < 0.001). Therefore, nationality should be considered in optimizing pacing strategy in Ironman triathlon.